DEMOGRAPHICS AND CHARACTERISTICS OF PATIENTS WITH TRAUMATIC BONE CYSTS: A RETROSPECTIVE REVIEW - Yavuz Tolga Korkmaz; Burak Cezairli; Turgay Peyami Hocaoğlu (Cumhuriyet University, 2017)
Objectives:  The aim of this study was to evaluate the demographics and characteristics of the patients treated for traumatic bone cyst (TBC). Materials and Methods: A retrospective review was conducted to determine the radiological, clinical and demographic characteristics of patients with TBC who were surgically treated over a 2-year period using data retrieved from computerized databases. Results: The study sample consisted of 22 patients (24 lesions in total) with mean age of 22.9 years. All lesions were located in the mandible (16 in anterior mandible, 8 in posterior mandible) and diagnosed incidentally during routine dental examinations. There was no statistically significant difference between male and female patients in demographic characteristics. All patients were followed up for 6-18 months with uneventful healing. Conclusions: TBCs should be kept in mind during examination of radiolucent lesions of the mandible particularly in younger patients. Along with the histopathological examination, clinical and radiological findings, symptoms of the patients, and surgeon's experience should be considered for a definitive diagnosis.